Hydroxyapatite based hybrid dental materials with controlled porosity and improved tribological and mechanical properties. (April 2013) - Vargas, S.; Estevez, M.; Hernandez, A.; Laiz, J. C.; Brostow, W.; Hagg Lobland, H. E.; Rodriguez, J. R.
Abstract : Hybrid dental materials were designed with controlled porosity and improved tribological and mechanical properties. These materials are based on hydroxyapatite (HAp) and reinforced with two different types of ceramic particles, alumina and silica, to support the high stresses and the continuous scratching produced during mastication. The agglutinant phase is an alkyd polyester polyurethane with high abrasion resistance that adheres well to surfaces containing OH groups. Porosity of the materials was controlled using sodium acetate powder of specified particle size as a pore former, thereby providing the materials with a morphology that resembles real teeth. The composition, structure and morphology were evaluated through several analytical techniques; results of scanning electron microscopy, dynamic light scattering, Fourier transform infrared spectroscopy, X-ray diffraction, induced coupled plasma optical emission spectroscopy and densitometry are reported. The ceramic powders incorporated (HAp, alumina and silica) were a combination of micro- and nanoscale particles; this use of different sized particles improved the packing and consequently the mechanical and tribological properties of the dental materials. Tribological features are explained from results of microscratch testing and abrasion resistance. The elastic modulus from mechanical testing is compared for the entire set of hybrid dental composites developed.